A combined voltammetric and synchrotron radiation-grazing incidence X-ray diffraction study of the electrocrystallization of zinc tetracyanoquinodimethane - Veder, J.; Nafady, A.; Clarke, G.; De Marco, Roland; Bond, A. (2012)
The in situ electrocrystallization of zinc tetracyanoquinodimethane (TCNQ) has been explored using synchrotron radiation-grazing incidence X-ray diffraction (SR-GIXRD) at potentials in the region of the cyclic voltammetric peak where reduction of TCNQ to TCNQ– occurs at a Pt electrode in acetonitrile (0.1 M [NBu4][PF6]) solution containing Zn(NO3)2·6H2O. The in situ SR-GIXRD data along with ex situ IR and Raman spectroscopy results all confirmed the formation of the kinetically favoured phase of Zn[TCNQ]2(H2O)2 as the product.